Allele Phasing Greatly Improves the Phylogenetic Utility of Ultraconserved Elements. (15th May 2018) - Andermann, Tobias; Fernandes, Alexandre M; Olsson, Urban; Töpel, Mats; Pfeil, Bernard; Oxelman, Bengt; Aleixo, Alexandre; Faircloth, Brant C; Antonelli, Alexandre
Abstract: Advances in high-throughput sequencing techniques now allow relatively easy and affordable sequencing of large portions of the genome, even for nonmodel organisms. Many phylogenetic studies reduce costs by focusing their sequencing efforts on a selected set of targeted loci, commonly enriched using sequence capture. The advantage of this approach is that it recovers a consistent set of loci, each with high sequencing depth, which leads to more confidence in the assembly of target sequences. High sequencing depth can also be used to identify phylogenetically informative allelic variation within sequenced individuals, but allele sequences are infrequently assembled in phylogenetic studies. Instead, many scientists perform their phylogenetic analyses using contig sequences which result from the de novo assembly of sequencing reads into contigs containing only canonical nucleobases, and this may reduce both statistical power and phylogenetic accuracy. Here, we develop an easy-to-use pipeline to recover allele sequences from sequence capture data, and we use simulated and empirical data to demonstrate the utility of integrating these allele sequences to analyses performed under the multispecies coalescent model. Our empirical analyses of ultraconserved element locus data collected from the South American hummingbird genus Topaza demonstrate that phased allele sequences carry sufficient phylogenetic information to infer the genetic structure, lineage divergence, and biogeographic history of a genus that diversified during the last 3 myr. The phylogenetic results support the recognition of two species and suggest a high rate of gene flow across large distances of rainforest habitats but rare admixture across the Amazon River. Our simulations provide evidence that analyzing allele sequences leads to more accurate estimates of tree topology and divergence times than the more common approach of using contig sequences.